Age, height and weight of top-level gymnasts in 2018 - Moznik, M. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
The objective of the study was to determine the differences in age, body height and body weight of top-level men gymnast among particular disciplines in 2018. Sample consisted of top eight qualifiers for each discipline at the 2018 World Championships in Doha. Variables were gymnasts age, body height and body weight, available on official FIG website. The data were analysed by the statistical package Statistica 12. Differences were calculated by ANOVA for independent sample. Results shown that there are no statistically significant differences in between disciplines, but there are some differences that exist. The biggest differences were in variable age. The youngest gymnasts were on the floor (21,75 y.o.), while the oldest gymnasts were on the rings (25,88 y.o.). The lowest (162,5 cm) and the lightest (57,33 kg) gymnasts were on the vault, the tallest gymnasts were on the pommel horse (169,71 cm) and the gymnasts with the highest body weight were on the still rings (65,2 kg). Results have been compared with the previous studies. In the future we can expect that the trend of specialization will continue so it`s necessary to conduct more detailed researches of anthropometry of the best gymnasts for a particular discipline.